Detection of metabolites of benzo(a)pyrene in Sorbus sibirica Hedl. leaves and their use in the assessment of air pollution of Kemerovo City (Russian Federation) - Neverova, OA; Bykov, AA; Legoshina, OM (Bangladesh Journal of Botany, 2013)
This article analyzes the ability of woody plants to metabolize benzapyrene and shows the assessment of the level of long-term air pollution in the city of Kemerovo by benzapirene from the industrial area with the help of modelling approach. Metabolites of benzo(a)pyrene - B(a)P-1,3-dione, 1-hydroxy-B(a)P and B(a)P- 7,8- dihydrodiol are identified in extracts of Sorbus sibirica Hedl. leaves. It is found that there is a close correlation between the sum of relative abundance of hydroxyl derivatives of benzapyrene (?OH-B(a)P) of S. sibirica leaves and air pollution by benzapirene (Q). DOI: http://dx.doi.org/10.3329/bjb.v42i1.15905 Bangladesh J. Bot. 42(1): 145-153, 2013 (June)